2007
DOI: 10.1007/bf03086017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of CFVR and FFR versus perfusion scintigraphy in patients with multivessel disease

Abstract: Objective. In this multicentre study, we investigated the long-term prognostic value of intracoronary derived haemodynamic parameters compared with the results of myocardial perfusion scintigraphy (MPS). Keywords: coronary artery disease, myocardial perfusion scintigraphy, coronary flow velocity reserve, fractional flow reserve, angioplasty, risk stratification A dequate patient selection for percutaneous transluminal coronary angioplasty (PTCA) is important in view of the potential procedural complications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…These patients were enrolled in a series of study protocols, 6,7,15,16 and patient and procedural characteristics were entered into a dedicated database. The study protocols excluded patients with ostial stenoses, serial stenoses, severe renal function impairment (glomerular filtration rate calculated according to the modification of diet in renal disease formula <30mL/min per 1.73 m 2 ), significant left main coronary artery stenosis, atrial fibrillation, recent myocardial infarction (<6 weeks before screening), prior coronary artery bypass graft surgery, or visible collateral development to the perfusion territory of interest.…”
Section: Data Sourcementioning
confidence: 99%
“…These patients were enrolled in a series of study protocols, 6,7,15,16 and patient and procedural characteristics were entered into a dedicated database. The study protocols excluded patients with ostial stenoses, serial stenoses, severe renal function impairment (glomerular filtration rate calculated according to the modification of diet in renal disease formula <30mL/min per 1.73 m 2 ), significant left main coronary artery stenosis, atrial fibrillation, recent myocardial infarction (<6 weeks before screening), prior coronary artery bypass graft surgery, or visible collateral development to the perfusion territory of interest.…”
Section: Data Sourcementioning
confidence: 99%
“…These patients were enrolled in a series of study protocols, [6][7][8][9] and patient and procedural characteristics were entered into a dedicated database. We excluded patients with ostial lesions, ≥2 stenoses in the same coronary artery, severe renal function impairment (glomerular filtration rate calculated according to the Modification of Diet in Renal Disease formula <30 mL/min per 1.73 m 2 ), significant left main coronary artery stenosis, atrial fibrillation, recent myocardial infarction (<6 weeks before screening), prior coronary artery bypass graft surgery, or visible collateral development to the perfusion territory of interest.…”
Section: Study Populationmentioning
confidence: 99%
“…In the same study two patients had positive exercise tests and one patient a positive Thallium SPECT scan with FFR values significantly above .75. Later studies have confirmed that a FFR results can have a prognostic significance which can be better than SPECT in a selected group of patients with untreated intermediate lesions after PCI of a severe lesion [2].…”
mentioning
confidence: 84%
“…In the same study two patients had positive exercise tests and one patient a positive Thallium SPECT scan with FFR values significantly above .75. Later studies have confirmed that a FFR results can have a prognostic significance which can be better than SPECT in a selected group of patients with untreated intermediate lesions after PCI of a severe lesion [2].In contrast SPECT itself has a significant prognostic value in patients with low or intermediate risk of coronary disease and has been recommended as a first line diagnostic method in coronary disease by the UK National Institute of Clinical Excellence (http:// www.nice.org.uk/nicemedia/pdf/TA073guidance.pdf). A normal Myocardial SPECT scan has been shown in large studies to have a very good prognostic value with adverse event rates of 0.6%/year quoted in one study of 7,376 consecutive patients [3].…”
mentioning
confidence: 85%